The role of age, sex, and multimorbidity in 7-year change in prevalence of limitations in adults 60–94 years - Benjamin Landré; Andres Gil-Salcedo; Louis Jacob; Alexis Schnitzler; Aline Dugravot; Séverine Sabia; Archana Singh-Manoux (Scientific Reports, 2022)
Abstract Recent data suggest a temporal trend in decline in functional limitations in older adults but whether this trend extends to the period after the 8th decade of life remains unclear. We examined change in prevalence of limitations in activities and instrumental activities of daily living (ADL and IADL) between 2008 and 2015 among adults of 60–94 years and the role of age, sex, multimorbidity; we also examined changes in severity of limitations. Data were drawn from two nationally representative surveys in 2008 (n = 13,593) and 2015 (n = 13,267). The 6-item scales of ADL and IADL were each categorized first as ≥ 1 limitations, and then to examine severity as 0, 1–2, and ≥ 3 limitations. Weighted logistic and multinomial regressions were used to estimate prevalence of limitations; the difference between surveys were extracted every 5 years between 60 and 90 years. The prevalence of ≥ 1 ADL declined between 2008 and 2015, from age 75 (− 1.2%; 95%CI = − 2.0, − 0.4%) to age 90 (− 8.8%; 95%CI = − 12.7, − 5.0%). This decline was more pronounced in men than women (p-value for interaction = 0.05) and observed primarily in those with multimorbidity (p-value for interaction = 0.06). Up to 2 ADL limitations declined from age 75 (− 1.0; 95%CI = − 1.7, − 0.3) to 90 (− 6.7; 95%CI = − 9.9, − 3.6) and from age 80 (− 0.6; 95%CI = − 1.1, 0.1) to 85 (− 1.2; 95%CI = − 2.2, − 0.1) for ≥ 3 ADL limitations. There was no substantial change in IADL limitations. These data from a high-income country with universal health care show improvement in ADL even after the 8th decade of life despite increase in multimorbidity.